Moonlight - Savage, Stephen, 1965- (New York City : Holiday House, 2022)
In the quiet hours of the night, moonlight makes its journey through the sky, over land and water, and finally into a child's bedroom.
"A Neal Porter Book."
new kids book 2022 fall.
Ages 4 to 8.
Grades K-1.
Keywords: Night -- Fiction; Bedtime -- Fiction; Moon -- Fiction; Picture books